A representação social da gestão de portfólio de projetos - Gomes, Alexandre de Deus (2016)
This study aims to develop an exploratory and qualitative/quantitative research about the social representation of Project Portfolio Management. The work aims to expose Project Portfolio Management perceptions between project users. To support the theoretical study, empirical data were collected through online questionnaires to 211 professionals in project’s field. Using the technique of word retrieval and the theory of social representation (TRS), the data collected were summarized. After processing the data using the technique of Vergès’ four-frame houses, the identification of the central nucleus and peripheral system of social representation of Project Portfolio Management was obtained as a result. Finally, data were analyzed using content analysis, so that all the data was compared for best interpretation of the theme. Obtained as a result, the core of the social representation of Project Portfolio Management consists of the following words are obtained as a result: 'Strategy', 'Organization' and 'Planning'. In turn, the words identified as part of the peripheral system of social representation of Project Portfolio Management were 'Objective', 'Time' and 'Process'. The results allow us to understand Project Portfolio Management' perception between project users and its correlation with the theoretical framework discussed. Such information and insights can help make the unfamiliar in familiar, i.e., understand how Project Portfolio Management is represented, seen, and finally recognized by professionals in the field of Project.